Synthetic DNA: methods and protocols - Hughes, Randall A. (Methods in molecular biology, 2017)
A Guide to Using STITCHER for Overlapping Assembly PCR Applications -- Synthetic Gene Design Using Codon Optimization On-Line (COOL) -- Shuffle Optimizer: A Program to Optimize DNA Shuffling for Protein Engineering -- Simple Cloning by Prolonged Overlap Extension PCR with Application to the Preparation of Large-Size Random Gene Mutagenesis Library in Escherichia coli -- SpeedyGenes: Exploiting an Improved Gene Synthesis Method for the Efficient Production of Error-corrected, Synthetic Protein Libraries for Directed Evolution -- BASIC - A Simple and Accurate Modular DNA Assembly Method -- Enzymatic Synthesis of Single Stranded Clonal Pure Oligonucleotides -- Rapid Assembly of DNA via Ligase Cycling Reaction (LCR) -- PaperClip: A Simple Method for Flexible Multi-part DNA Assembly -- The Polymerase Step Reaction (PSR) Method for Gene and Library Synthesis -- Clonetegration Using OSIP Plasmids - One Step DNA Assembly and Site Specific Genomic Integration in Bacteria -- Generation of DNA Constructs Using the Golden GATEway Cloning Method -- Gene Deletion by Synthesis in Yeast -- Efficient Assembly of DNA Using Yeast Homologous Recombination (YHR) -- Simultaneous Removal of Multiple DNA Segments by Polymerase Chain Reactions -- Rapid Construction of Recombinant Plasmids by QuickStep-Cloning -- Immobilized MutS-mediated Error Removal of Microchip-synthesized DNA -- Selection of Error-less Synthetic Genes in Yeast.
Keywords: Chemische Synthese; DNS